STUDY OF INCREASING COMMUNITY WELFARE THROUGH OPTIMIZING HUMAN CAPITAL IN LANGKAT DISTRICT - Diwayana Putri Nasution (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to determine factors (income, consumption, education, capital, number of dependents, production experience on the welfare of fishermen's families in Pantai Cermin Village, Tanjung Pura District, Langkat Regency. The number of samples used was 200 families. The data was collected by distributing questionnaires and data processing. using Multiple Linear Regression Analysis.High unemployment, low education, low wages, greatly affect the welfare of the people in Langkat district.The results of multiple linear regression testing, the results of partial hypothesis testing show that consumption, experience, production and the number of dependents are significant to the welfare of fishermen in Pantai Cermin Village, Tanjung Pura District.